Beyond Monuments: Rethinking Heritage Through the Mundane and the Ephemeral in Tokyo - Tamas Solymosi (Ochrona Dziedzictwa Kulturowego, 2024)
As global cities rapidly evolve, conventional approaches to architectural heritage conservation struggle to address the complexities of contemporary urban landscapes. This paper critically examines the limitations of the Venice Charter's monument-centric principles in recognizing the cultural significance of vernacular architecture, ephemeral spaces, and community narratives that shape the lived experiences of Tokyo's residents. Grounded in critical heritage theory and ethnographic research, it proposes an alternative set of principles that acknowledge the inherent value of the mundane, the utilitarian, and the ephemeral aspects of the built environment.